Basic Engineering Properties of Laminated Veneer Lumber Produced from Tropical Hardwood Species - H'ng, Paik San (2003)
One of the reasons for a limited structural usage of L VL in tropical countries is the lack of research and development to establish design criteria for this material. Such information is essential for the development of design values as well as new structural uses of LVL.. This study aimed to establish basic engineering properties of L VL produced from selected tropical hardwood species i.e. Yellow Meranti (Shorea spp.), Kedondong (Conarium spp), Bintangor (Calophylhlm spp ), White Meranti horea spp.), and Kerning (Dipterocarpus spp). Tests for static bending, bending shear, tensile and compression parallel to longitudinal axis were carried out using in-grade size specimens. The tests were conducted in accordance withASINZS 4357 (Structural Laminated Veneer Lumber). The effects of two important factors (I) wood species and (2) veneer thickness, on the strength properties of LVL were studied. The results show that Kerning LVL has the highest density (700 - 820 kglm3), followed by White Meranti (600-680 kg/m Bintangor (570-590 kg/m, Kedondong (545-574 kg/m3) and Yellow Meranti (510-541 kg/m3). Using thinner veneers increased the LVL panel density between 2.8% (in Kedondong) to 8.9% (in Kerning). Despite having lower board density. both White Meranti and Bintangor LVLs had significantly superior engineering properties than those made from Keruing, Kedondong and Yellow Meranti. Keruing LVL performed below the expectation in all the strength properties which was attributed to the poor bond quality observed through the gluebond shear test and scanning electron microscope analysis.